2010
DOI: 10.1371/journal.pone.0013209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic and Epigenetic Marks Involved in Population Structure

Abstract: Population structure is well known as a prevalent and important factor in genetic studies, but its relevance in epigenetics is unclear. Very little is known about the affected epigenetic markers and their connections with genetics. In this study we assessed the impact of population diversity on genome wide single nucleotide polymorphisms (SNPs) and DNA methylation levels in 196 participants from five ethnic groups, using principle and independent component analyses. Three population stratification factors (PSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…The most significant association was obtained with two SNPs, known as being strongly correlated with both blue and brown eye colours, located within HERC2 gene (rs1129038 and rs12913832; P-value ¼ 4.99 Â 10 À37 ). Other significant associations (P-valueo5 Â 10 À8 ) were found with both CTNNA2 (OMIM: 114025) 6 and OCA2 genes.…”
Section: Resultsmentioning
confidence: 90%
“…The most significant association was obtained with two SNPs, known as being strongly correlated with both blue and brown eye colours, located within HERC2 gene (rs1129038 and rs12913832; P-value ¼ 4.99 Â 10 À37 ). Other significant associations (P-valueo5 Â 10 À8 ) were found with both CTNNA2 (OMIM: 114025) 6 and OCA2 genes.…”
Section: Resultsmentioning
confidence: 90%
“…41 Furthermore, through principal and independent component analyses, Liu et al 41 found that the population structure present in DNA methylation data are very well captured by the first genetic principal component. Hence, to avoid confounding effects due to population stratification, we applied principal component analysis to our genotype data using EIGENSTRAT of the EIGENSOFT 3.0 software package, 42,43 and included the first principal component as covariate in our imaging models.…”
Section: Behavioral Taskmentioning
confidence: 99%
“…A first one highlighted significant differences in global genomic DNA methylation of peripheral blood cells by ethnicity, suggesting that this individuals' information should be accurately considered in every methylation study (Zhang et al, 2011). The second one instead tried to assess the impact of population SNPs diversity patterns at the genome-wide level on DNA methylation profiles (Liu et al, 2010). For this purpose, around 200 samples of different self-reported ethnicity were analysed for 1M SNPs and for methylation status at 27 000 CpGs distributed across the whole genome.…”
Section: The Population Epigenetics Approachmentioning
confidence: 99%